Efficient Irrigation for Florida-Friendly Edible Landscapes - Jacqlyn Rivas; Tiare Silvasy; Luke Harlow; Lynn Barber; Jennifer W. Marvin; Esen Momol; Tina McIntyre; Terra Freeman (EDIS, 2022)
This new 7-page publication is written for Florida gardeners, homesteaders and other horticulturalists interested in planting and establishing edible landscapes and improving those landscapes by conserving water. This publication will provide guidance for choosing the ideal irrigation system for edible cropping systems as well as general tips for conserving water in edible landscapes. https://edis.ifas.ufl.edu/ep617